Additional file 1 of Deploying new generation sequencing for the study of flesh color depletion in Atlantic Salmon (Salmo salar) - Thu Thi Minh Vo (11148654); Tuan Viet Nguyen (11148657); Gianluca Amoroso (3560942); Tomer Ventura (277255); Abigail Elizur (39766) (2021)
Additional file 1: Supplementary 1. Distribution of GO terms and the most significant GO terms in comparison of TruSeq and QuantSeq library.